Dielectric and Microwave Properties of Siloxane Rubber/Carbon Black Nanocomposites and Their Correlation - Omar A. Al-Hartomy; Falleh Al-Solamy; Ahmed Al-Ghamdi; Nikolay Dishovsky; Vladimir Iliev; Farid El-Tantawy (International Journal of Polymer Science)
In this paper, the dielectric and microwave properties of carbon black/siloxane rubber-based nanocomposites have been investigated in the frequency range from 1 GHz till 12 GHz according to the content of carbon black and the frequency. It has been established that the increasing frequency and filler content lead to an increase in the relative permittivity and tangent of dielectric loss angle. At higher filler content, the effects become more pronounced, especially those upon dielectric loss. It has been also established that there are two well-distinguished areas in all dependences of microwave properties on frequency and filler content increasing. The first is between 1 and 8 GHz wherein the reflection and attenuation of microwaves do not change considerably with frequency and filler content alternation while shielding effectiveness worsens. The second area is between 8 and 12 GHz wherein the reflection and attenuation of microwaves increase drastically with the increasing frequency and filler content. Shielding effectiveness improves, too. It has been established that in all cases the degree of correlation between dielectric and microwave properties evaluated on the basis of the coefficients of correlation calculation is perfect.